Development of Judo Basic Techniques Based on the Video Kodomo No-Kata on School Age Children - Ita Rahmawati; Abdul Rachman Syah Tuasikal; Achmad Widodo (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Kodomo No Kata is made for children who want to learn the basics of judo. Consisting of a prologue and seven units or seven levels, Kodomo No Kata covers all the moves and techniques that must be mastered at each level. Each unit consists of a dropping technique (ukemi), moving places (Tai sabaki), and a slamming/throwing technique (nagewaza), a holding technique (osaekomi waza). With the ongoingpandemic, Covid 19which resulted in the imposition of Community Activity Restrictions (PPKM) which made school-age children unable to exercise regularly and had to comply with health protocols. One alternative for children to be able to exercise and practice judo is to practice judo techniques independently using tools that are around, anywhere, anytime, both under normal and pandemic conditions based on the video Kodomo No Kata. This study aims to develop basic judo techniques based on the video Kodomo No Kata for school-aged children (6-14 years). This research is a research and development method which is often called R&D (Research and Development). The small group test was conducted on the athletes of the Judo Club Judo Cendana Surabaya, the large group test was carried out on the athletes of the City of Surabaya, the Mojokerto Regency Government and the Mojokerto City Council. The result is a video product of basic judo technique training which is carried out independently using existing tools, equipped with a guide book as a support.